Productivity spillovers from multinational activity to indigenous firms in Ireland - Mattia Di Ubaldo; Martina Lawless; Iulia Siedschlag (The Economic and Social Research Institute (ESRI), 2018)
As well as their direct effects on output and employment, the attraction of foreign direct investment is sometimes argued to provide further economic benefits through spillover effects that potentially increase the productivity performance of domestic firms. Empirical evidence on this has however tended to be mixed. This paper uses Irish firm-level data on both manufacturing and services firms to re-examine and update tests of intraindustry and intra-region spillovers and then extends the previous research by examining if spillovers are more likely to occur through supply chain linkages. We further test for the sensitivity of these vertical spillover effects to alternative supply chain measures. Overall, we find fairly limited evidence of a link between the presence of foreign-owned firms and the performance of domestic firms with considerable sensitivity of results to changes in specification. Important variation across sectors is identified, however, with more robust evidence of intra-industry spillovers on the productivity performance of firms in services. Examining forward and backward linkages through supply chains indicates some negative impacts from obtaining supplies from and supplying foreign-owned firms although these are mitigated for domestic firms which invest in R&D, which appears to increase the absorptive capacity of the firms to benefit from productivity spillovers.
Keywords: F23; D22; O33; 330; Foreign direct investment; productivity spillovers; absorptive capacity